A imagem da política: implicações das propagandas políticas nas escolhas eleitorais no Rio de Janeiro - Mariana Lopes Alves; Sérgio da Silva (Ciências Sociais Unisinos)
TThe aim of the present paper is to analyze the mechanisms and elements present in the construction of the politician is image during the electoral process. This is crucial to understand, not only the logics reproduced by the candidates to get the position of a representative in the executive power, but also, the means of the image transmitted to the electorate that will support the democratic choices of the population. The empirical analysis was based on the esthetic and discourse elements that composed the electoral advertising campaigns for the election of the State of Rio de Janeiro.